A study on non-performing assets and their impact on public and private sector banks - CHERUKUR, MR. RAMBABU; MS. LEKHASHREE.V, (The journal of contemporary issues in business and government, 2020)
Banks are struggling with challenges related to NPA’s. The objective of the study is to examine the reasons for the rising NPAs and its impact on public and private sector banks.The research findings were analysed using tools like frequency analysis, mean analysis and ANOVA analysis.The sample size of the study is 83 and respondents were customers of the bank.This paper focuses on the reasons behind the NPA and its impact on public and private sector banks.